Оцінка продуктивності алгоритмів адаптивного формування променю Smart-антени для систем мобільного зв’язку 5G - Андрущенко, О. В.; Шумков, І. М.; Москалець, М. В. (ХНУРЕ, 2022)
The synthesis of mathematical model of linear antenna array in MATLAB software package is presented. The results of mathematical modeling are presented. The analysis and comparison of the performance of LMS and RLS algorithms is carried out. Various criteria were considered in the comparison, including amplitude response (grating coefficient), convergence time, acquisition and tracking of the desired useful signal. Recommendations on the applicability of Smart-antenna technologies in 5G New Radio mobile communication systems are given.
Keywords: продуктивність адаптивне формування променю Smart-антени системи мобільного зв’язку 5G